The Diverse Collection of Exotic Tropical Fruits in The Indonesian Tropical Fruit Research Institute (ITFRI) - Nasution, Fitriana; Hadiati, Sri (Journal of Tropical Horticulture, 2020)
Indonesian Tropical Fruit Research Institute (ITFRI) known as an institute collecting exotic tropical fruits in Indonesia. The present study was carried to evaluate the characters of five exotic fruits in the Indonesian Tropical Fruit Research Institute (ITFRI), Solok, West Sumatra, Indonesia. The experiment used field observation. The characters considered were leaf character (leaf shape, leaf margin, leaf tip, leaf base, the color of upper leaf, color of under leaf, leaf surface, leaf length, leaf width), and fruit character (fruit shape, fruit peel texture, fruit length, fruit width, fruit weight, the color of mature peel, the color of mature flesh, taste, fruit weight, seed weight, seed number). Data were analyzed descriptively using tables. The five exotic fruits' morphological characteristics have demonstrated that every species of fruit has specific characteristics. These fruits have the potential to be raw materials for the pharmacy industry.